IBM Rational Application Developer V6 Portlet Application Development and Portal Tools - Rodriguez, Juan; Cesario, Cristiano; Galvan, Karla; Gonzalez, Belen; Kroner, George; Rutigliano, Gianfranco; Wilson, Ryan (IBM Redbooks, 2005)
This IBM Redbook provides an overview and hands-on scenarios to help you design, develop and implement portlet applications using Rational Application Developer V6.0 and the provided Portal Tools. The sample scenarios included in this redbook target Business-to-Employee (B2E) enterprise applications, but most of the scenarios presented will also apply to Business-to-Consumer (B2C) applications. You will find step-by-step examples and scenarios showing ways to integrate your enterprise applications into an IBM WebSphere Portal environment using the WebSphere Portal APIs provided by the Portal Tools to develop portlets. You will also learn how to extend your portlet capabilities to use advanced functions such as cooperative portlets, internationalization, action events, using the Credential Vault to enable Single Sign-On, Web Services, remote portlets, portal design and portlet debugging capabilities. Elements of the Portlet API and the standard JSR168 API are described and sample code is provided. The scenarios included in this redbook can be used to learn about portlet programming and as a basis for your own portlet applications. You will also find scenarios describing recommended ways to develop portlets and portlet applications that follow the MVC design pattern, the Struts framework and JavaServer Faces technology. Basic knowledge of Java technologies such as servlets, JavaBeans, EJBs, JavaServer Pages (JSPs), as well as of XML applications and the terminology used in Web publishing, is assumed.